2001
DOI: 10.1080/02724930123814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of education and training on neonatal resuscitation practices in 14 teaching hospitals in India

Abstract: The impact of a neonatal resuscitation programme (NRP) on the incidence, management and outcome of birth asphyxia was evaluated in 14 teaching hospitals in India. Two faculty members from each institution attended a neonatal resuscitation certification course and afterwards trained staff in their respective hospitals. Each institution provided 3 months pre-intervention and 12 months post-intervention data. Introduction of the NRP significantly increased awareness and documentation of birth asphyxia, as judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 4 publications
3
51
1
3
Order By: Relevance
“…36 Nine studies (20%) attempted to correlate performance on either standardized tests or actual behavior in the delivery room with changes in neonatal mortality statistics, and the results were mixed. 18,30,31,37,42,60,62,64,73 Four (44.4%) of these studies documented significant declines in neonatal mortality correlating with improvement in test scores and delivery room behavior, respectively. 30,31,42,60 Five studies (55.6%) reported no improvement in mortality despite improvement in test scores and/or delivery room behavior.…”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 99%
See 1 more Smart Citation
“…36 Nine studies (20%) attempted to correlate performance on either standardized tests or actual behavior in the delivery room with changes in neonatal mortality statistics, and the results were mixed. 18,30,31,37,42,60,62,64,73 Four (44.4%) of these studies documented significant declines in neonatal mortality correlating with improvement in test scores and delivery room behavior, respectively. 30,31,42,60 Five studies (55.6%) reported no improvement in mortality despite improvement in test scores and/or delivery room behavior.…”
Section: Impact Of Theoretical Knowledge On Delivery Room Behaviors Amentioning
confidence: 99%
“…25, 36, 38, 39, 48, 49, 59, 61, 62, 71, 73 -75 Sixteen studies (35.6%) evaluated clinical behavior in the delivery room in addition to, or instead of, testing birth attendants in simulated scenarios. In 10 (62.5%) of these studies, examiners directly observed birth attendants, 18,30,31,36,43,44,59,64,65 whereas in 7 studies (43.8%), scores were based on chart review or recall by birth attendants and/or the newborn's mother. 37,43,47,50,57,60,62 One study both directly observed birth attendants and surveyed community women cared for by these attendants.…”
Section: Description Of Articlesmentioning
confidence: 99%
“…61 Extensive efforts to train physicians in neonatal resuscitation, for example using WHO and American Academy of Pediatrics-American Heart Association Neonatal Resuscitation Program materials, are underway in many developing countries, and are showing encouraging results in influencing behavior. 62,63 Few studies, however, especially community-based studies, have assessed the risk factors, causes and sequelae of birth asphyxia in developing countries, and few have evaluated appropriate methods to train health workers and family members at the community level to recognize birth asphyxia and provide simple interventions and support.…”
Section: Immediate Newborn Carementioning
confidence: 99%
“…19 In ten university hospitals in India, the introduction of the Resuscitation Program reduced early neonatal mortality from 31 to 24 per 1,000 live births and the incidence of hypoxic-ischemic encephalopathy by 70%. 17 Theoretical and practical training in neonatal resuscitation also results in short term benefits for the newborn, including improvements in Apgar Scores. 20 It is within this context that the present study is situated, in attempting to find out how neonatal resuscitation training is given to students soon to qualify as physicians, pediatricians, neonatologists and nurses at public maternity As can be observed in the results, the hospitals and maternity units studied were predominantly public.…”
Section: Discussionmentioning
confidence: 99%
“…Around 6 to 10% of live births need immediate respiratory care, but, once spontaneous respiration has been established, the majority of these infants survive with no need for other life support measures. [16][17][18] According to the World Health Organization, 8 education and training in resuscitation offer the possibility of immediately applying recent scientific advances to reduce neonatal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%